Great Muslim mathematicians - Mohaini Mohamed (UTM, 2000)
This book presents detailed accounts and analysis of the lives and world view of selected mathematicians of the Islamic period, their place in the world of science, the popularization of their lives, and their contributions specifically in mathematics and astronomy.